Online Availability - Gruen, Thomas; Corsten, Daniel (Springer, 2019)
This chapter presents a research study of online availability (OLA) in six non-food consumer goods categories (baby care, fabric care, hair care, oral care, skin care, and shave care) at online and omnichannel retailers in six major countries (China, France, Germany, Japan, UK, and USA). It provides insight into the extent of online availability (OLA) and its opposite non-online availability (NOLA) using data from online retailers’ websites, reports from surveys of online shoppers, and surveys from managers of online retail and branded goods manufacturers. It illuminates online shoppers’ encounters with NOLA and reactions to it with a detailed examination of switching behavior to alternative options. It estimates the lost sales opportunities and provides guidelines for improving OLA.
Keywords: Availability; Omnichannel; Online retail; Stock-out; Out-of-stock; Shopper switching behavior; 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura